1998
DOI: 10.1046/j.1525-1497.1998.00025.x
|View full text |Cite
|
Sign up to set email alerts
|

A prediction rule for the use of postdischarge medical services

Abstract: OBJECTIVE:To develop and validate a prediction rule screening instrument, easily incorporated into the routine hospital admission assessment, that could facilitate discharge planning by identifying patients at the time of admission who are most likely to need postdischarge medical services. DESIGN:Prospective cohort study with separate phases for prediction rule development and validation. SETTING: Urban teaching hospital. PATIENTS/PARTICIPANTS:General medical service patients, 381 in the derivation phase and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
1
20
0
2
Order By: Relevance
“…In addition, this association showed a dose-response with the increase in odds of increasing dependence increased gradually with increasing age. In the elderly, patient-reported functional limitation predicts mortality 22 , post-discharge medical services usage 23 , and nursing home placement 24 . These functional limitations were seen in a third of all patients at 2- and 5-years after primary THA, which indicates a significant burden of disability in these elderly patients after primary THA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this association showed a dose-response with the increase in odds of increasing dependence increased gradually with increasing age. In the elderly, patient-reported functional limitation predicts mortality 22 , post-discharge medical services usage 23 , and nursing home placement 24 . These functional limitations were seen in a third of all patients at 2- and 5-years after primary THA, which indicates a significant burden of disability in these elderly patients after primary THA.…”
Section: Discussionmentioning
confidence: 99%
“…Using the National Long Term Care Survey, Murtaugh and Litke (2002) found a prevalence rate of 24 percent for potential transition-related problems over a two-year time period, defined as emergency department visits, hospital admissions, and returns to an institutional setting following discharge to the community. Fairchild and colleagues developed a predictive index designed to identify patients who may require the use of postdischarge medical services; however, the index was constructed using a single study population (i.e., patients hospitalized at an urban teaching hospital) and relied on predictor variables that are not routinely available in the hospital setting (Fairchild et al 1998). Prior studies have demonstrated that indices that utilize administrative or self-reported data have similar rates of predictive accuracy (Coleman et al 1998;Roblin et al 1999;Fethke, Smith, and Johnson 1986;Anderson and Steinberg 1985;Mukamel et al 1997;Roos et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patient-centered HRQoL measures are used as global assessments of functional status and overall perceptions of health [2], and have been proposed as measures of disease severity. For example, the SF-36 predicts mortality in patients following coronary artery bypass graft surgery [3], successful treatment of chronic low back pain [4], and postdischarge medical services [5]. The SF-36 also has been used to predict 1-year total health plan expenses in a health maintenance organization [6,7].…”
Section: Introductionmentioning
confidence: 99%